Digital risk on international business / Etty Harniza Harun, Musdiana Mohamad Salleh and Hasni Abdul Rahim - Harun, Etty Harniza; Mohamad Salleh, Musdiana; Abdul Rahim, Hasni (Universiti Teknologi MARA, Kedah, 2022)
The digitalization era that brings about an increase in the digital connectivity has bring great advantage to the expansion of international business in the past decades. Many benefits already sought by multinational enterprises (MNEs) from the expansion, however the widespread in the digital world does bring about challenge risk of its own. With the widespread of digitalization, there is an increase need to a proper risk management technique to protect companies having their operations abroad. In this article, focus made on the explanation of the three (3) types of digital risks generally faced by MNEs pertaining to digitalization that are the digital interdependence risk, global information and security risk and also the digital regulatory complexity risk.